PENGEMBANGAN WEBSITE LAYANAN “DIGIKEPO” (STUDI DIGITALISASI LAYANAN E-KTP DI KECAMATAN DOLOPO KABUPATEN MADIUN) - Nur Suci Kirana Wati, Rendita; Lestari, Yuni (Jurnal Inovasi Administrasi Negara Terapan, 2023)
Services provided by government agencies to the public to solve problems and enforce the law are considered public services. This research plans to build an online service in Dolopo Sub-district by using the ADDIE technique, which consists of the following five steps: analysis, design, development, implementation, and assessment. The final aim of this research is to create a digital administration system for Dolopo sub-district. An R&D approach was used to collect data to develop this service. Based on the results of the study, it is found that the development of DIGIKEPO services consists of usability, feasibility, accuracy and compliance, in terms of usability, namely: the application can help services, the application section is easy to understand, the description on each button is easy to use, the application system can run, and the application can help. In terms of feasibility: the color in the application, making the whatsapp application easier, the DIGIKEPO application is feasible to use, and the completeness of the condiment, in terms of accuracy: application display, layout composition, color composition, media size, and selected fonts. In terms of appropriateness: application media according to manufacture, application media does not violate norms, illustrations or images are appropriate, the language used is Indonesian and the DIGIKEPO application has a positive value. This can be seen from the results of the average validation value of media experts of 85, material expert validation of 86. Furthermore, community respondents of 88.4% showed "very good" criteria. Based on the results of the study, it can be concluded that the DIGIKEPO application has been used at the Dolopo District Office and during operation there are no obstacles in its use.   Keywords: Public Service;E-government;Digitalization